2019
DOI: 10.1212/nxg.0000000000000366
|View full text |Cite
|
Sign up to set email alerts
|

GNA11 brain somatic pathogenic variant in an individual with phacomatosis pigmentovascularis

Abstract: ObjectiveTo describe the findings of histopathology and genotyping studies in affected brain tissue from an individual with phacomatosis pigmentovascularis (PPV). MethodsA retrospective chart review of a 2-year 10-month-old male with a clinical diagnosis of PPV cesiomarmorata (or type V) was performed. Clinical features, brain imaging and histopathology findings, and genotyping studies in his affected brain tissue are summarized. pigmentovascularis brain somatic pathogenic variant in an individual with phacoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Finally, two patients with PPV type II or cesioflammea died, however as both cases were referred to us for genotyping due to the severity of clinical disease, this is likely to be a higher incidence than a true prospective cohort figure. One of these died in infancy, with recurrent apnea and classical changes of SWS on magnetic resonance imaging (MRI) and magnetic resonance angiography (MRA) (recently reported in detail; Sliepka et al, 2019), and the second died in adulthood, after sudden onset of multiple intracranial hemorrhages with no discoverable underlying MRI/MRA vascular abnormality and no hypertension.…”
mentioning
confidence: 99%
“…Finally, two patients with PPV type II or cesioflammea died, however as both cases were referred to us for genotyping due to the severity of clinical disease, this is likely to be a higher incidence than a true prospective cohort figure. One of these died in infancy, with recurrent apnea and classical changes of SWS on magnetic resonance imaging (MRI) and magnetic resonance angiography (MRA) (recently reported in detail; Sliepka et al, 2019), and the second died in adulthood, after sudden onset of multiple intracranial hemorrhages with no discoverable underlying MRI/MRA vascular abnormality and no hypertension.…”
mentioning
confidence: 99%
“…Subsequent transgenic mosaic zebrafish models expressing GNA11 R183C showed dermal melanocytosis mimicking human phenotype 14 . These findings were later validated by several case reports detecting GNAQ/GNA11 mosaic‐activating variants in PPV patients 7,15–18 . The majority of reported variants hotspots were GNA11 c.547C>T (p.R183C) and GNAQ c.548G>A (p.R183Q).…”
Section: Introductionmentioning
confidence: 65%
“…A literature search was conducted on PubMed for articles reporting somatic variants in PPV patients until January 31, 2023. Six studies were identified, detecting somatic GNAQ/GNA11 variants in 13 out of 17 patients with PPV 7,14–18 . Thomas et al 14 reported three additional patients with extensive dermal melanocytosis but without lesions, two of whom had a GNAQ variant.…”
Section: Resultsmentioning
confidence: 99%
“…Port wine stain (PWS), a kind of congenital capillary malformation, can be manifested as one or several bright red or dark red patches, which are more common on the head and face. As time goes by, these lesions may darken and hypertrophy, 1 which will have a serious negative impact on the patient's appearance, physical, and mental health 2 . Pulsed dye laser (PDL) is the preferred treatment for PWS, but the PDL‐induced angiogenesis is an important factor influencing outcome 3 .…”
Section: Introductionmentioning
confidence: 99%
“…As time goes by, these lesions may darken and hypertrophy, 1 which will have a serious negative impact on the patient's appearance, physical, and mental health. 2 Pulsed dye laser (PDL) is the preferred treatment for PWS, but the PDL-induced angiogenesis is an important factor influencing outcome. 3 According to studies, as the laser targets the blood vessels, the body will be repairing itself simultaneously, of which vascular regeneration is an important part.…”
Section: Introductionmentioning
confidence: 99%